Dynamics Of Two Coupled, Nonlinear, Autonomous 4ᵗʰ Order Circuits - Papadopoulou, Maria S.; Kyprianidis, Ioannis M.; Stouboulos, Ioannis N. (İstanbul Kültür Üniversitesi Yayınları, 2006)
In this paper we have studied the case of chaotic synchronization of two identical, mutually coupled, non linear, 4th order autonomous electric circuits. Each circuit contains one linear negative conductance G and one non linear resistür RNwith a symmetrical piecewise-linear v-i characteristic. Using the capacitances Ci and Ci as the control parameters, we have observed the transition from periodic states to chaotic ones and vise versa, as well as crisis phenomena. We have established the mutual coupling via a variable resistür Rx.We have observed that synchronization is possible as the resistance of the coupling element is varied.
Keywords: Shaotic Synchronization; Autonomous Circuit; Control Parameter; Crisis; Mutual Coupling; Kaotik Senkronizasyon; Özerk Devre; Kontrol Parametresi; Kriz; Karşılıklı Birleştirme